-8B+1+6B=-3B+6

Simple and best practice solution for -8B+1+6B=-3B+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8B+1+6B=-3B+6 equation:


Simplifying
-8B + 1 + 6B = -3B + 6

Reorder the terms:
1 + -8B + 6B = -3B + 6

Combine like terms: -8B + 6B = -2B
1 + -2B = -3B + 6

Reorder the terms:
1 + -2B = 6 + -3B

Solving
1 + -2B = 6 + -3B

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Add '3B' to each side of the equation.
1 + -2B + 3B = 6 + -3B + 3B

Combine like terms: -2B + 3B = 1B
1 + 1B = 6 + -3B + 3B

Combine like terms: -3B + 3B = 0
1 + 1B = 6 + 0
1 + 1B = 6

Add '-1' to each side of the equation.
1 + -1 + 1B = 6 + -1

Combine like terms: 1 + -1 = 0
0 + 1B = 6 + -1
1B = 6 + -1

Combine like terms: 6 + -1 = 5
1B = 5

Divide each side by '1'.
B = 5

Simplifying
B = 5

See similar equations:

| [2-6(8-5)]= | | 4(B-7)=6B-28 | | m=n/9 | | 7x^2+29x-30= | | -4(-3)+4(6)+3(-2)= | | 7B+4=8(B+1) | | 3Z-2Z+16=4 | | a^2-16ab+63b^2=0 | | 8-5x=-7x+10 | | v-14=u | | 9x^4-6x^3+7/-9x^4=0 | | 2y+3=14 | | 15b^2+6b-3= | | 5x^2=3x+2 | | 7x-5=22-2x | | x^2+5x+6=09 | | -7tx=b-3y | | 108z+3-64z+5= | | 25x^2=30x-9 | | 0=3x^2-17x+20 | | -3x^6+6x^6= | | Z-2(1-Z)-2Z= | | 6x^8+4x^8= | | 3(Y-2)-2(Y-6)= | | -15=x^2+8x | | -1/7+Y=5/7 | | 10x^8+3x^6= | | 6=7b-pb | | 50c+349-200=400 | | 28x^2-18x+72=0 | | -2v-22=-8(v-1) | | -2(u+6)=-8u+48 |

Equations solver categories